2019
DOI: 10.1139/cjfas-2018-0142
|View full text |Cite
|
Sign up to set email alerts
|

Size-specific apparent survival rate estimates of white sharks using mark–recapture models

Abstract: For species that exist at low abundance or are otherwise difficult to study, it is challenging to estimate vital rates such as survival and fecundity and common to assume that survival rates are constant across ages and sexes. Population assessments based on overly simplistic vital rates can lead to erroneous conclusions. We estimated sex- and length-based annual apparent survival rates for white sharks (Carcharodon carcharias). We found evidence that annual apparent survival differed over ontogeny in a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Similarly, differences in life-history traits between adult males and females of other taxa contribute to the observed sex-specific differences in survival (Weimerskirch et al 1997, Frederiksen et al 2005, Xavier et al 2005. For instance, Kanive et al (2015Kanive et al ( , 2019 reported a male biased adult sex ratio in white sharks (Carcharodon carcharias) and suggested this finding may be the result of differential male/female mortality earlier in life or emigration of females. These studies highlight the importance of research on the potential causes of sex ratio bias across species.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, differences in life-history traits between adult males and females of other taxa contribute to the observed sex-specific differences in survival (Weimerskirch et al 1997, Frederiksen et al 2005, Xavier et al 2005. For instance, Kanive et al (2015Kanive et al ( , 2019 reported a male biased adult sex ratio in white sharks (Carcharodon carcharias) and suggested this finding may be the result of differential male/female mortality earlier in life or emigration of females. These studies highlight the importance of research on the potential causes of sex ratio bias across species.…”
Section: Accepted Articlementioning
confidence: 99%
“…Yet, patterns of movement influence the susceptibility of animals to both natural and anthropogenic mortality by dictating the magnitude of interactions with various threats (Fossette et al 2014, Frick et al 2017). Consequently, identifying the magnitude of these threats remains a central goal of many studies (Hays et al 2016, Kanive et al 2019). For example, a group that attracts both huge conservation effort and concern is sea turtles, where adults face a number of threats, including direct capture for human consumption, incidental capture (bycatch) through various fishing activities, and mortality through boat strikes (Rees et al 2016, Frick et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have investigated the connection between various life‐history strategies and survival rates in monophyletic groups, especially in long‐lived vertebrates (Sacher, 1978), and the relationships among life‐history traits seem to be better understood in females than males (Festa‐Bianchet, 2012). Because it is challenging to obtain sex‐ and age‐specific survival data in long‐lived vertebrate species (Hupman et al., 2018; Kanive et al., 2019; Lebreton et al., 1992), empirical data on survival rates for multiple species in a monophyletic group are limited. For groups with adequate data, information is also needed on measurement errors in life‐history traits (either through pseudoreplication or through standard errors on measurements from a single study) and evolutionary pathways so that uncertainties in these measurements can be incorporated into the comparative analyses (Ives et al., 2007; Revell & Reynolds, 2012; de Villemereuil et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1a). Though juvenile white sharks 2.5-3.0 m TBL are detected north of Point Conception 13,14,28 , neonate, YOY, and other juveniles < 2.5 m TBL sharks in the Monterey Bay remained nonexistent or extremely rare until 2014 15 . Partly in response to these events, and out of concern for public safety at beaches, in 2018 the California State Senate passed funding measures (SB 840) to expand population monitoring of white sharks at popular recreation areas 29 .…”
mentioning
confidence: 99%